PERBANDINGAN UNJUK KERJA COAP DAN HTTP PADA TRANSAKSI DATA PERANGKAT IOT - Hendro FJ Lami; Stephanie I. Pella (Jurnal Media Elektro, 2022)
Internet of Things (IoT) is the interconnection of several devices that have specific tasks such as sensing and control. The services in the system can be in the form of one device - one service, many devices - one service, one device -many services, and many devices - many services. A communication protocol is agreed upon by the devices in the IoT system to ensure the success of data transactions. These protocols include MQTT, HTTP, AMQP, XMPP, Web Shocket, and COAP. This study compares the performance of the COAP and HTTP protocols in consideration of the number of transactions and energy consumption. The scenario used is to send RSSI data and battery level. The scenarios also use two modes of transmission power:14dBm and 20dBm. The results show that the COAP protocol is 25 times more efficient than the HTTP protocol for a 20dBm transmit power scenario, while for a transmit power of 14dBm COAP is 61 times